Probiotic Lactobacillus rhamnosus GG Promotes Mouse Gut Microbiota Diversity and T Cell Differentiation - Shi, Chun-wei; Cheng, Ming-yang; Yang, Xin; Lu, Yi-yuan; Yin, Hong-duo; Zeng, Yan; Wang, Ru-yu; Jiang, Yan-long; Yang, Wen-tao; Wang, Jian-zhong; Zhao, Dan-dan; Huang, Hai-bin; et al. (Frontiers in Microbiology, 2020)
Lactic acid bacteria (LAB) are the primary genera of the intestinal flora and have many probiotic functions. In the present study, Lactobacillus rhamnosus GG (LGG) ATCC 53103 was used to treat BALB/c mice. After LGG intervention, both low and high LGG doses were shown to improve the observed OTU, Chao1, ACE, and Shannon indices, while the Simpson index decreased, demonstrating that LGG can promote intestinal microbiota abundance and diversity. Furthermore, LGG treatment increased the abundances of intestinal Firmicutes, Bacteroides and Actinomycetes while reducing that of Proteobacteria. In addition to its effect on gut the microbiota, LGG could also regulate the host immune system. In the present study, we showed that LGG could affect the percentage of CD3+ T lymphocytes in the spleens (SPLs), mesenteric lymph nodes (MLNs), Peyer’s patches (PPs) and lamina propria lymphocytes (LPLs) of mice, including total CD3+ T, CD3+CD4+ T and CD3+CD8+ T lymphocytes. Furthermore, LGG could effectively increase the expression of Th1-type cytokines (IFN-γ) and Th2 cytokines (IL-4) in CD4+ T cells, indicating that the proportion of Th1 and Th2 cells in mice with LGG treatment was in a high equilibrium state compared to the control group. In addition, the IFN-γ/IL-4 ratio was greater than 1 in mice with LGG intervention, suggesting that LGG tends to mediate the Th1 immune response. The results of the present study also showed that LGG upregulated the expression of IL-17 in CD4+ T cells and regulated the percentage of CD4+CD25+Foxp3+ Treg cells in various secondary immunological organs, indicating that LGG may promote the balance of Th-17 and Treg cells.